Modelling to inform next-generation medical interventions for malaria prevention and treatment - Narimane Nekkab; Josephine Malinga; Lydia Braunack-Mayer; Sherrie L. Kelly; R. Scott Miller; Melissa A. Penny (Communications Medicine, 2023)
Nekkab, Malinga, Braunack-Mayer et al. discuss how modelling can be incorporated early on in the research and development of malaria tools alongside clinical evidence and expert opinion. In addition, population models can provide estimates of potential effectiveness of novel interventions to inform product criteria and support decision-making.